2013
DOI: 10.3354/meps10387
|View full text |Cite
|
Sign up to set email alerts
|

Delayed settling of marine snow at sharp density transitions driven by fluid entrainment and diffusion-limited retention

Abstract: Marine snow is central to the marine carbon cycle, and quantifying its small-scale settling dynamics in different physical environments is essential to understanding its role in biogeochemical cycles. Previous field observations of marine aggregate thin layers associated with sharp density gradients have led to the hypothesis that these layers may be caused by a decrease in aggregate settling speed at density interfaces. Here, we present experimental data on aggregate settling behavior, showing that these part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 56 publications
6
69
1
Order By: Relevance
“…The results support previous studies showing that aggregates may decrease their settling velocity when passing through a density transition (Kindler et al, 2010;Camassa et al, 2013;Prairie et al, 2013). The present study further examines the relationship between stratification and delayed settling behavior; individual aggregates were compared across multiple density gradients to isolate the effect of density gradient from the natural variation in aggregate size, shape, and composition.…”
Section: Trends and Mechanisms For Delayed Settlingsupporting
confidence: 80%
See 3 more Smart Citations
“…The results support previous studies showing that aggregates may decrease their settling velocity when passing through a density transition (Kindler et al, 2010;Camassa et al, 2013;Prairie et al, 2013). The present study further examines the relationship between stratification and delayed settling behavior; individual aggregates were compared across multiple density gradients to isolate the effect of density gradient from the natural variation in aggregate size, shape, and composition.…”
Section: Trends and Mechanisms For Delayed Settlingsupporting
confidence: 80%
“…NMSV ranged from less than 0 (indicating the aggregate came to a full stop) to 0.72. The few slightly negative NMSV values observed here are within video recording noise, although we note that in some cases in previous studies (e.g., Abaid et al, 2004 andLin, 2009 for solid particles; Prairie et al, 2013 for aggregates), particles have been observed to temporarily reverse direction at sharp density gradients. DSTS also displayed a large range among aggregates, spanning almost two orders of magnitude from 4.4 to 271.7.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…This Theme Section contains 8 studies with topics ranging from hotspots of marine snow to migratory top predators. Prairie et al (2013) in a laboratory experiment demonstrated mechanisms by which particles can be temporarily retained when encountering density gradients. The density of the aggregate relative to the density of the bottom layer in the gradient is the primary determinant of the extent that marine snow will aggregate, thereby enhancing food web development at the boundary layer.…”
Section: Contributions To the Theme Sectionmentioning
confidence: 99%